Acidification Enhances Hybrid N2O Production Associated with Aquatic Ammonia-Oxidizing Microorganisms - Frame, Caitlin H.; Lau, Evan; Nolan, E. Joseph; Goepfert, Tyler J.; Lehmann, Moritz F. (Frontiers in Microbiology, 2017)
Ammonia-oxidizing microorganisms are an important source of the greenhouse gas nitrous oxide (N2O) in aquatic environments. Identifying the impact of pH on N2O production by ammonia oxidizers is key to understanding how aquatic greenhouse gas fluxes will respond to naturally occurring pH changes, as well as acidification driven by anthropogenic CO2. We assessed N2O production rates and formation mechanisms by communities of ammonia-oxidizing bacteria (AOB) and archaea (AOA) in a lake and a marine environment, using incubation-based nitrogen (N) stable isotope tracer methods with 15N-labeled ammonium (15NH4+) and nitrite (15NO2-), and also measurements of the natural abundance N and O isotopic composition of dissolved N2O. N2O production during incubations of water from the shallow hypolimnion of Lake Lugano (Switzerland) was significantly higher when the pH was reduced from 7.54 (untreated pH) to 7.20 (reduced pH), while ammonia oxidation rates were similar between treatments. In all incubations, added NH4+ was the source of most of the N incorporated into N2O, suggesting that the main N2O production pathway involved hydroxylamine (NH2OH) and/or NO2- produced by ammonia oxidation during the incubation period. A small but significant amount of N derived from exogenous/added 15NO2- was also incorporated into N2O, but only during the reduced-pH incubations. Mass spectra of this N2O revealed that NH4+ and 15NO2- each contributed N equally to N2O by a ‘hybrid-N2O’ mechanism consistent with a reaction between NH2OH and NO2-. Nitrifier denitrification was not an important source of N2O. Isotopomeric N2O analyses in Lake Lugano were consistent with incubation results, as 15N enrichment of the internal N versus external N atoms produced site preferences (25.0‰ to 34.4‰) consistent with NH2OH-dependent hybrid-N2O production. Hybrid-N2O formation was also observed during incubations of seawater from coastal Namibia with 15NH4+ and NO2-. However, the site preference of dissolved N2O here was low (4.9‰), indicating another mechanism, not captured during the incubations, was important. Multiplex sequencing of 16S rRNA revealed distinct ammonia oxidizer communities: AOB dominated numerically in Lake Lugano, and AOA dominated in the seawater. Potential for hybrid N2O formation exists among both communities, and at least in AOB-dominated environments, acidification may accelerate this mechanism.